Association of health and lifestyle factors with uterine fibroids among Saudi women: A case–control study. Issue 6 (December 2022) - Muawad, Reema; Dabbagh, Rufaidah; Sabr, Yasser
الملخص: أهداف: الهدف من هذه الدراسة هو قياس العلاقة بين تليف الرحم وعوامل الخطر المختلفة (تعدد الولادات، الإجهاض، السكري، ارتفاع ضغط الدم، النشاط البدني، التدخين، التاريخالعائلي لالتهاب الرحم، واستخدام حبوب منع الحمل) بين النساء السعوديات. طرق: أجريت دراسة الحالات والشواهد في مركزين طبيين في الرياض، بين امرأة. تم تأكيد الحالات عن طريق الموجات فوق الصوتية. تم جمع المعلومات الديموغرافية وعوامل الخطر من خلال المقابلة والسجلات الطبية. تم حساب انتشار عوامل الخطر المختلفة مع فاصلة ثقة ٩٥٪. تم استخدام تحليل الانحدار اللوجستي غير المشروط لقياس الارتباط بين تليف الرحم وعوامل الخطر المختلفة. نتائج: كان أكثر من نصف المشاركين يعانون من السمنة المفرطة. كان متوسط مؤشر كتلة الجسم للحالات ٣١.٢ (±٦.٨١)، بينما كان٢٩.٤ (±٧.٠٢) للشواهد. كان لدى النساء اللواتي يبلغن من العمر ٤٠ عامًا فما فوق أربع أضعاف احتمالات الإصابة بتليف الرحم مقارنة بالنساء الأصغر من ٤٠ عامًا (نسبه الأرجحية المصحح ٤.٢٤ بفاصلة ثقة ٩٥٪ بين ٢.٦٣ و٦.٨٥(ارتبط وجود تاريخ عائلي لتليف الرحم مع احتمالات متزايدة بالإصابة بتليف الرحم بنسبة ٦٩٪ (نسبه الأرجحية المصحح ١.٦٩ بفاصلة ثقة ٩٥٪ بين ١.٠٢ و٢.٨١ (. ارتبطت السمنة بزيادة احتمالات الإصابة بتليف الرحم بنسبة ٧٤٪ (نسبه الأرجحية المصحح ١.٧٤ بفاصلة ثقة ٩٥٪ بين ١.٠٠ و٢.٥٩)، بينما قللت الولادات السابقة من احتمالات الإصابة بتليف الرحم بنسبة ٦٢٪ (نسبه الأرجحية المصحح ٠.٣٨، بفاصلة ثقة ٩٥٪ بين ٠.١٩ و٠.٧٥(. الاستنتاجات: ساعدت هذه الدراسة في تحديد بعض عوامل الخطر المرتبطة بتليف الرحم في النساء السعوديات. العمر فوق ٤٠ عامًا، والسمنة والتاريخ العائلي من تليف الرحم هي عوامل خطر مهمة للتليف الرحم، بينما يبدو أن تعدد الولادات يحمي من الإصابة بتليف الرحم في النساء السعوديات. التعرف المبكر على عوامل الخطر مهم لمنع مضاعفات تليف الرحم. Abstract: Objectives: The objective of this study was to measure the association between uterine fibroids (UFs) and several risk factors (parity, miscarriage, diabetes, hypertension, physical activity, smoking, family history of UF and contraceptive pill use) among Saudi women. Methods: A case–control study was conducted in 478 women at two medical centers in Riyadh. Cases were confirmed by ultrasound. Demographic and risk factor information was collected from interviews and medical records. The prevalence of risk factors was calculated with 95% confidence interval (CI). Unconditional logistic regression analysis was used to measure the associations between UFs and the risk factors. Results: More than half the participants were obese. The average body mass index (BMI) was 31.2 (±6.81) for cases and 29.4 (±7.02) for controls. Women 40 years or older had four times the odds of UFs than women younger than 40 years (adjusted odds ratio [AOR] = 4.24, 95% CI = 2.63, 6.85). Having a family history of UFs was associated with 69% greater odds of UFs (AOR = 1.69, 95% CI = 1.02, 2.81). Being obese was associated with 74% greater odds of UFs (AOR = 1.74, 95% CI = 1.00, 2.59), whereas previous live births decreased the odds of UFs by 62% (AOR = 0.38, 95% CI = 0.19, 0.75). Conclusions: This study identified risk factors associated with UFs in the Saudi population. Age over 40 years, obesity and a family history of UFs are important risk factors for UF, whereas parity appears to be protective against UF development in Saudi women. Early recognition of these risk factors is important to prevent UF complications.